Influence of Copper Resistance Determinants on Gold Transformation by Cupriavidus metallidurans Strain CH34 - Wiesemann, Nicole (American Society for Microbiology, 2013)
Cupriavidus metallidurans is associated with gold grains and may be involved in their formation. Gold(III) complexes influence the transcriptome of C. metallidurans (F. Reith et al., Proc. Natl. Acad. Sci. U. S. A. 106:17757–17762, 2009), leading to the upregulation of genes involved in the detoxification of reactive oxygen species and metal ions. In a systematic study, the involvement of these systems in gold transformation was investigated. Treatment of C. metallidurans cells with Au(I) complexes, which occur in this organism's natural environment, led to the upregulation of genes similar to those observed for treatment with Au(III) complexes. The two indigenous plasmids of C. metallidurans, which harbor several transition metal resistance determinants, were not involved in resistance to Au(I/III) complexes nor in their transformation to metallic nanoparticles. Upregulation of a cupA-lacZ fusion by the MerR-type regulator CupR with increasing Au(III) concentrations indicated the presence of gold ions in the cytoplasm. A hypothesis stating that the Gig system detoxifies gold complexes by the uptake and reduction of Au(III) to Au(I) or Au(0) reminiscent to detoxification of Hg(II) was disproven. ZupT and other secondary uptake systems for transition metal cations influenced Au(III) resistance but not the upregulation of the cupA-lacZ fusion. The two copper-exporting P-type ATPases CupA and CopF were also not essential for gold resistance. The copABCD determinant on chromosome 2, which encodes periplasmic proteins involved in copper resistance, was required for full gold resistance in C. metallidurans. In conclusion, biomineralization of gold particles via the reduction of mobile Au(I/III) complexes in C. metallidurans appears to primarily occur in the periplasmic space via copper-handling systems.